The relationship between non-alcoholic fatty liver disease and acute coronary syndrome severity: is non-alcoholic fatty liver disease a risk marker of coronary atherosclerotic disease?. (14th October 2021) - Soares Sturzeneker, M C; Montemezzo, M; Precoma, D B; De Noronha, L; Kluthcovsky, A C G C; Lipinski, L C; De Oliveira, P G M; Viechineski, F N; Koscianski, A L
Abstract: Background/Introduction: Non-alcoholic fatty liver disease (NAFLD) has been significantly associated with atherosclerotic disease independent of classical risk factors. However, the role of NAFLD in this context remains unclear. The systemic inflammation described in NAFLD related to liver disease progression may be one factor that can influence the progression and instability of atherosclerotic disease and, consequently, in the clinical characteristics of acute coronary syndrome (ACS). Purpose: To assess the potential relationship between NAFLD and ACS severity. Methods: We performed a retrospective study in adult patients with ACS who presented to the emergency room of a quaternary care medical centre between March 2015 and March 2016 and selected 99 patients without previously known coronary artery disease or liver disease, without a history of significant alcohol consumption, terminal disease, other acute illness, use of statins, amiodarone, or other steatogenic drugs. The diagnostic criteria for acute myocardial infarction (AMI) with ST-segment elevation (STEMI) were ST elevation ≥1mm in ≥2 contiguous leads (2mm for leads V1 to V3). The acute myocardial infarction without ST-segment elevation (NSTEMI) diagnostic was established in patients who did not meet the criteria for STEMI and who had elevated necrosis markers (creatine kinase-MB isoform and troponin I). Unstable angina (UA) diagnostic was established in patients who did not meet the criteria for STEMI and NSTEMI but had more than three cardiovascular risk factors and typical thoracic pain. The presence of steatosis and its degrees was assessed using ultrasound, and the diagnosis of NAFLD was based on the presence of steatosis and clinical history. Results: The diagnosis of UA, NSTEMI and STEMI was established in 40, 33 and 26 patients, respectively, and NAFLD was observed in 30%, 66.6% and 76.9% of these patients. NAFLD patients were 5.8 times more likely to have a diagnosis of AMI than UA (p<0.001), were 7.88 times more likely to have a diagnosis of STEMI than UA (p<0.001) and were 4.7 times more likely to have a diagnosis of NSTEMI than UA (p<0.01). Patients with grades 2 and 3 liver steatosis were 4.2 times more likely to have a diagnosis of AMI than UA (p<0.01) and were 8.2 times more likely to have a diagnosis of STEMI than UA (p<0.01). There was no significant relationship between other variables evaluated and the clinical presentation of ACS. Conclusion(s): In this study, the frequency of AMI presentation in NAFLD patients with ACS was significantly higher than the frequency of UA, suggesting a significant relationship between NAFLD and the severity of ACS, independent of the classic risk factors assessed. The results also suggest that the steatosis degree can proportionally influence this context. Therefore, NAFLD could be considered a potential risk marker for coronary atherosclerotic disease progression and instability. Funding Acknowledgement: Type of funding sources: None.